Identification des flux de civelles (Anguilla anguilla) à partir des relations d’allométrie en fonction des conditions hydrodynamiques de l’estuaire de l’Adour - De Casamajor, Marie-noelle; Prouzet, Patrick; Lazure, Pascal (Gauthier-villars/editions Elsevier, 2000)
Biological data on glass eels (Anguilla anguilla) were collected during two successive sampling periods from November to March (1996-1997 and 1997-1998) on the Adour estuary. As for other estuaries, decrease in length (mean of 73.5 to 67.4 mm) and weight (mean of 3.5 to 2.6 dg) of glass eels were observed. Weight and length characteristics were used to identify groups of glass eels. These groups were well distinguished during the first sampling period but some overlaps appeared in the second one. Fluctuations of static allometry and similarity coefficients showed successive glass eels arrivals in the lower part of the estuary during the two seasons. We used fluctuations of the index of similarity in the second period to describe arrivals of glass-eels groups. The conjunction of strong floods and weak tide coefficients leads to unfavourable conditions of migration for the glass eels penetrating the estuary. After accumulation of shoals of glass eels in the lower part of the estuary, when hydrological conditions become again favourable. the mixed shoals migrate again by successive 'waves', at the rhythm of tides. (C) 2000 Ifremer/CNRS/INRA/IRD/Cemagref/Editions scientifiques et medicales Elsevier SAS. Les caractéristiques biologiques des civelles (Anguilla anguilla) ont été étudiées entre novembre et mars lors de deux campagnes d’échantillonnage successives (1996–1997 et 1997–1998) dans l’estuaire de l’Adour. Une diminution de la longueur (en moyenne de 73,5 à 67,4 mm) et du poids (en moyenne de 3,5 à 2,6 dg) des civelles durant la saison de migration est observée comme sur les autres estuaires. Différents groupes de civelles peuvent être identifiés au cours de chaque saison étudiée. Les variations du coefficient d’allométrie statique et de l’indice de similarité indiquent l’arrivée successive de différents flux dans le bas estuaire. Ces groupes sont bien différenciés lors de la première campagne alors qu’ils se chevauchent dans le temps lors de la seconde. La conjonction de forts débits fluviaux et de faibles ...